2017
DOI: 10.1161/jaha.117.006453
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Status and the Risk of Cerebrovascular Events Following Radiation Therapy for Head and Neck Cancer

Abstract: BackgroundRadiation therapy (RT) is a standard treatment for head and neck cancer; however, it is associated with inflammation, accelerated atherosclerosis, and cerebrovascular events (CVEs; stroke or transient ischemic attack). Human papillomavirus (HPV) is found in nearly half of head and neck cancers and is associated with inflammation and atherosclerosis. Whether HPV confers an increased risk of CVEs after RT is unknown.Methods and ResultsUsing an institutional database, we identified all consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…The role of HPV as a pathogen likely extends beyond cancer promotion, as a growing number of studies have found associations between HPV and increased risks of pregnancy complications and cardiovascular diseases [29][30][31]. This study found active HPV gene expression in placentae in PETcomplicated pregnancies, suggesting that HPV genes capable of affecting cell function are expressed in PET associated placentae.…”
Section: Discussionsupporting
confidence: 50%
“…The role of HPV as a pathogen likely extends beyond cancer promotion, as a growing number of studies have found associations between HPV and increased risks of pregnancy complications and cardiovascular diseases [29][30][31]. This study found active HPV gene expression in placentae in PETcomplicated pregnancies, suggesting that HPV genes capable of affecting cell function are expressed in PET associated placentae.…”
Section: Discussionsupporting
confidence: 50%
“…There are several limitations to this study. First, some potential confounding factors were not available for analysis, including data on human papillomavirus and radiotherapy-induced toxicity which have been shown to be associated with cerebrovascular events following RT [12][13][14]. Smoking is also an important risk factor for stroke [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, besides the potential effect of HPV infection, it is necessary to consider also the potential local and systemic late side effects of radiotherapy—vascular damage associated with endothelial degeneration, splitting of the basal membrane, deposition of lipids, adventitial fibrosis, and occlusion of the lumen of arteries [14,15]. On the other hand, in patients with malignancy of head and neck after radiotherapy, the risk of strokes was increased four-fold in the case of HPV-positive tumours compared with the patients with HPV-negative tumours [16]. Moreover, a recent case report documented atypical presentation of cervical carcinoma, which was diagnosed secondarily in a 30-year-old patient who was hospitalised due to ischaemic stroke while no traditional risk factors were present [17].…”
Section: Cardiovascular Disease Associated With Hpv Infectionmentioning
confidence: 99%